Concomitant SLAP repair does not influence the surgical outcome for arthroscopic Bankart repair of traumatic shoulder dislocations - (:unkn) unknown (SAGE PUBLICATIONS INC, 2017)
Background: Prior studies revealed the presence of superior labrum anterior-to-posterior (SLAP) injury together with Bankart lesions in some patients. The purpose of the study is to compare the clinical results of isolated Bankart repairs with the clinical results of Bankart repairs when performed with concomitant SLAP repairs. Methods: The patients who underwent arthroscopic surgery for treatment of anterior glenohumeral instability were evaluated retrospectively. Group 1 consisted of 19 patients who had arthroscopic SLAP repair together with Bankart repair. The mean age of the patients was 23. Group 2 consisted of 38 patients who underwent isolated Bankart repair. The mean age was 24. Knotless anchors were used in both groups. Results: The mean follow-up was 34 months (range: 26-72). In group 1, the mean preoperative Constant score was 84 (range: 74-90, standard deviation (SD): 5.91) and Rowe score was 64.1 (range: 40-70, SD: 8.14). In group 2, the preoperative Constant score was 84.4 (range: 70-96, SD: 5.88) and Rowe score was 60 (range: 45-70, SD: 7.95). In group 1, the postoperative mean Constant score raised to 96.8 (range: 88-100, SD: 2.91) and the mean Rowe score raised to 92.3 (range: 85-100, SD: 5.17). In group 2, the postoperative mean Constant score was 94.9 (range: 88-100, SD: 3.70) and the mean Rowe score was 94.2 (range: 80-100, SD: 4.71). The difference between the scores of two groups was insignificant (p > 0.05). When the numbers of redislocations and range of motion were compared, no significant difference was found (p > 0.05). Conclusion: Accompanying SLAP repair in surgical treatment with Bankart repair for shoulder instability does not affect the results negatively. Properly repaired labral tears extending from anterior inferior to the posterior superior of the glenoid in instability treatment have the same outcome in overall results as repaired isolated Bankart lesions.
Keywords: arthroscopy; Bankart repair; instability; labrum; shoulder; slap; SUPERIOR LABRUM ANTERIOR; SUTURE ANCHORS; GLENOID LABRUM; LESIONS; INSTABILITY; BICEPS; COMPLEX; TEARS; JOINT